Techno-Sociopreneurship in the Merdeka Belajar era - Susetyarto, Martinus B. (Jurnal Entrepreneur dan Entrepreneurship, 2021)
“Techno-Sociopreneurship” is a combination of three words, namely “Technology,” “Social”, and “Entrepreneurship,” which is a process of forming and collaborating between business fields with first, the application of technology as a supporting instrument and as a basis for business, and second, the application of social values as a market network that needs each other in the society. The learning of Techno-Socioprenership in the Merdeka Belajar era is very important to improve the mastery of attitude, knowledge, methodology and skills. The participants are students of interdisciplinary study programs, across universities, culture, and social status, which united with one goal, namely to become reliable Indonesian entrepreneurs. A reliable entrepreneur is basically a person who dares to achieve the vision and mission of the business with hard work, energy, mind, soul and body. This article is done by library study research method. The aim is to present the Techno-Sociopreneurship learning model that can accommodate the combined process of courage or brave, system thinking, acting complexity management, business instincts, technological innovation, and social relation perspective, using modern homemade work tools, extracting material to solve problems. In the Techno-Sociopreneurship learning, the basics of sustainability and vice versa risk and uncertainty must be taught to achieve profit and growth by finding opportunities that exist with the best way.